2016
DOI: 10.3758/s13421-016-0588-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving encoding strategies as a function of test knowledge and experience

Abstract: Information that is produced or generated during learning is better remembered than information that is passively read, a phenomenon known as the generation effect. Prior research by deWinstanley and Bjork (Memory & Cognition, 32, 945-955, 2004) has shown that learners, after experiencing the memorial benefits of generation in the context of a fillin-the-blank test following the study of a text passage containing both to-be-read and to-be-generated items, become more effective encoders of to-be-read items on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
5
13
0
Order By: Relevance
“…The main effects of time on JOLs and actual learning performance are consistent with previous research indicating that the act of taking a test can reduce overconfidence (Yue et al, 2015) and improve encoding (Storm et al, 2016)—in this case, these effects occurred even when the material was delivered by a fluent or disfluent lecturer and when the content of the two tests (and videos) were unrelated.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The main effects of time on JOLs and actual learning performance are consistent with previous research indicating that the act of taking a test can reduce overconfidence (Yue et al, 2015) and improve encoding (Storm et al, 2016)—in this case, these effects occurred even when the material was delivered by a fluent or disfluent lecturer and when the content of the two tests (and videos) were unrelated.…”
Section: Discussionsupporting
confidence: 87%
“…However, this hypothesis was rendered moot as those in the fluent and disfluent conditions were equally overconfident—it is difficult to remedy an asymmetry that does not exist. That said, JOLs were lower for the second video across all three experiments indicating that the experience of taking a test can reduce overconfidence (Storm et al, 2016), even when the repeated tests cover different material. Further, in Experiment 2, we found that participants improved calibration for the second video, especially after a delay.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Namely, participants were less selective in their recall when their previous testing experience consisted of recognition tests than of recall tests. This would suggest that participants learned from testing and adjusted their strategies accordingly (Garcia-Marques et al, 2015; Jensen, McDaniel, Woodard, & Kummer, 2014; Storm et al, 2016). That RgRc participants were not as selective as the All Rc participants indicates that they did not learn to prioritize high-value items simply as a consequence of study design—such prioritization was unnecessary when their test performance was at ceiling—and thus did not have the same amount of practice executing a value-based strategy as those in the All Rc condition, for whom such a strategy was always important.…”
Section: Resultsmentioning
confidence: 99%